Pre-Trial Analysis of Wilayatul Hisbah Authority in Qanun Criminal Jurisdiction: A Study in Banda Aceh Syar'iyyah Court - Delta, Ria (Universitas Islam Sultan Agung, 2023)
Pretrial is a request submitted by a suspect, in the event that the actions carried out by law enforcement officials are contrary to the law, both in the investigation and prosecution process or in other words the coercive efforts carried out by investigators are contradictory. with the jinayat procedural law and the Criminal Procedure Code, because it is related to human rights. Pretrial is the authority of the district court to examine and decide whether or not an arrest and/or detention is legal, stop the investigation or stop the prosecution. This research aims to determine the authority of wilayatul hisbah in handling criminal acts by qanun in relation to the criminal justice system in Indonesia (Integrated Criminal Justice System). research through literature studies, but interviews with several informants who are considered to understand cases that occur during the implementation/enforcement of qanuns to the community are still needed. Often there is overlap in the resolution of handling qanun cases between the police and wilayatul hisbah in the same case, resulting in unclear handling of the case. Qanun is part of the Indonesian legal system which only applies in Aceh. The Aceh government can implement and implement Islamic law in social life because it is supported by a dynamic society, however in resolving criminal cases the Qanun experiences many obstacles and is not resolved properly so systemic improvements are needed, because it can enforce effective law. implemented if the 5 (five) Legal Pillars are running well, namely: Legal instruments or law enforcement officers, community members, legal regulations, cultural factors or legal culture, facilities and infrastructure that can support the good implementation of Qanun.